Diagnostic algorithms for acute ankle injury imaging - Trufanov, Gennadii E.; Aleksandrovich, Viktoria Y.; Menkova, Irina S. (Alʹmanakh klinicheskoĭ medit͡s︡iny, 2023)
Ankle trauma is the most prevalent low extremity injury among urgent referral patients. Up to 85% of acute ankle traumas lead to an isolated ligament injury, with up to 50% of these patients would have chronic pain syndrome in the future, related to inaccurate diagnosis and resulting inappropriate treatment strategy and rehabilitation term. We analyzed publications on the state-of-the-art aspects of radiation diagnostics of acute ankle injury available from PubMed/MEDLINE databases and in the Russian Index of Scientific Citation (Elibrary.ru) for the last ten years; some earlier essential publications on certain aspects were also considered. Up to now, there have been no unified guidelines on the radiation diagnosis of ankle injury depending on the trauma type, mechanism, and severity. The Ottawa ankle rules (1994) are the basic guidelines for selection of the patients with acute trauma who should be offered X-rays. Primary X-ray would allow for the choice of the treatment strategy or further diagnostic assessment of the patient. Computed tomography is done for multi-fragment intra-articular fractures and for the control after their reposition. Computed tomography is used in patients with severe pain syndrome and other absolute and relative contraindications for magnetic resonance imaging. The latter allows for the imaging of all injured structures within a single assessment procedure and by such to make the diagnosis of ligament and tendon ruptures, to visualize osteochondral injuries, hidden and stress fractures and many other acute ankle injuries. Ultrasound assessment can considerably add to clinical understanding of the patient during acute trauma, if magnetic resonance imaging is contraindicated. Based on the analysis performed, we propose the algorithms for diagnostic assessment in various clinical situations.